Answer :

To Prove: 3 sin–1x = sin–1 (3x – 4x3)

Proof: 

we know that,

sin3θ = 3 sinθ - 4 sin3θ.....(1)

Let sinθ = x, then

θ = sin-1 x

Put the value in equation 1, we get,

sin3θ = 3x - 4x3

3θ = sin-1(3x - 4x3)

3 sin–1x = sin–1 (3x – 4x3)

Hence, Proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers